Collaborative helping : a strengths framework for home-based services - Madsen, William C., 1954- (John Wiley & Sons, Inc., 2014)
"This book outlines a clear map for dealing with the complex and often ambiguous situations encountered by those working in supportive services. Drawing from numerous interviews with frontline helpers and people seeking help, this resource uses stories to introduce and illustrate core ideas and practices. Examining some of the common dilemmas of working with and advocating for the people served in home and community based settings, this unique volume explores how to collaborate with traditionally trained professionals across systems and how to involve people's natural networks and communities in helping endeavors"--